Outer Membrane Vesicles Derived From Escherichia coli Regulate Neutrophil Migration by Induction of Endothelial IL-8 - Lee, Jaewook; Yoon, Yae Jin; Kim, Ji Hyun; Dinh, Nhung Thi Hong; Go, Gyeongyun; Tae, Sookil; Park, Kyong-Su; Park, Hyun Taek; Lee, Changjin; Roh, Tae-Young; Di Vizio, Dolores; Gho, Yong Song (Frontiers in Microbiology, 2018)
Outer membrane vesicles (OMVs) are spherical, proteolipid nanostructures that are constitutively released by Gram-negative bacteria including Escherichia coli. While it has been shown that administration of E. coli OMVs stimulates a strong pulmonary inflammatory response with infiltration of neutrophils into the lungs in vivo, the mechanism of E. coli OMV-mediated neutrophil recruitment is poorly characterized. In this study, we observed significant infiltration of neutrophils into the mouse lung tissues in vivo, with increased expression of the neutrophil chemoattractant CXCL1, a murine functional homologue of human IL-8, upon intraperitoneal administration of E. coli OMVs. In addition, OMVs and CD31-positive endothelial cells co-localized in the mouse lungs. Moreover, in vitro results showed that E. coli OMVs significantly increased IL-8 release from human microvascular endothelial cells and Toll-like receptor (TLR)4 was found to be the main component for recognizing E. coli OMVs among human endothelial cell-associated TLRs. Furthermore, the transmigration of neutrophils was suppressed in the lung tissues obtained from TLR4 knock-out mice treated with E. coli OMVs. Taken together, our data demonstrated that E. coli OMVs potently recruit neutrophils into the lung via the release of IL-8/CXCL1 from endothelial cells in TLR4- and NF-κB-dependent manners.